2003
DOI: 10.1038/sj.pcan.4500637
|View full text |Cite
|
Sign up to set email alerts
|

Elements regulating angiogenesis and correlative microvessel density in benign hyperplastic and malignant prostate tissue

Abstract: Purpose: To quantify the ex vivo production of proangiogenic proteins (vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), urokinase-type plasminogen activator (u-PA), tissue-type plasminogen activator (tPA)) and angiogenesis inhibitors (plasminogen activator inhibitor type-1 (PAI-1) and angiostatin) from epithelial and stromal components of primary prostate cancer (CaP) and benign prostatic hyperplasia (BPH) cultures. To perform microvessel density (MVD) counts on sections of BPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In the future, immunohistochemical techniques [50,51] might elucidate more on the nature of the false readings. There are indications that (co-occurring) prostatitis or BPH might be responsible for false positives, as these diseases are known to also promote angiogenesis [52,53]. Qualitative inspection of the false negatives revealed that these were indeed invisible to the naked eye on all US modalities.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, immunohistochemical techniques [50,51] might elucidate more on the nature of the false readings. There are indications that (co-occurring) prostatitis or BPH might be responsible for false positives, as these diseases are known to also promote angiogenesis [52,53]. Qualitative inspection of the false negatives revealed that these were indeed invisible to the naked eye on all US modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, neprilysin-expressing LNCaP cells do not produce measurable amounts of FGF-2, in contrast to non-neprilysin-expressing, androgen-independent PC-3 and DU-145 cells (34). Fibroblast growth factor-2 is highly expressed in prostate cancer tissues (35)(36)(37), and expression correlates with neovascularization in prostate cancer tissue specimens (38). Patients with prostate cancer have significantly elevated serum FGF-2 levels compared with healthy controls that increase on progression to androgen-independent disease (35).…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have compared vascularization in normal prostate, BPH/LUTS, and cancer specimens. These studies have demonstrated increased microvessel density (MVD) in BPH/LUTS compared to normal prostate tissue (Deering et al, 1995) and even in BPH/LUTS compared to malignant tissue (Shih et al, 2003). These studies provide some rationale for exploring chemokine-mediated angiogenesis as a contributing factor to BPH/LUTS development and progression (Figure 1).…”
Section: Chemokines As Cytokines In Bph/lutsmentioning
confidence: 99%